Determination of seven anticoagulant rodenticides in human serum by ultra-performance liquid chromatography-mass spectrometry. Issue 5 (22nd January 2015) - Dong, Xinfeng; Liang, Shuxuan; Sun, Hanwen
Abstract : Anticoagulant rodenticide residues (warfarin, coumatetralyl, diphacinone, chlorophacinone, brodifacoum, bromadiolone, and flocoumafen) in human serum were determined by sensitive high-performance liquid chromatography-mass spectrometry. Abstract : A rapid, sensitive and selective method for simultaneous determination of seven anticoagulant rodenticide residues (warfarin, coumatetralyl, diphacinone, chlorophacinone, brodifacoum, bromadiolone, and flocoumafen) in human serum by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) has been developed and validated. Serum sample preparation was carried out rapidly and effectively by one-step protein precipitation and analytes extraction using methanol containing 10% acetone. Chromatographic separation was achieved within 10 min using a BEH C18 column (1.7 μm, 2.1 mm × 100 mm) and gradient elution with the mobile phase of 5 mM ammonium acetate aqueous solution–methanol. Good linearity was achieved over three orders of magnitude with a correlation coefficient ( r 2 ) of 0.9924–0.9994. The limits of detection for the seven rodenticides ranged from 0.06 μg L −1 (flocoumafen) to 1.5 μg L −1 (diphacinone). The intra- and inter-day relative standard deviations (RSDs) of the seven analytes at the three spiked levels (1 × LOQ, 5 × LOQ and 10 × LOQ) were in the range of 0.6–10.3% and 5.1–15.1%, respectively. The mean recoveries for the seven analytes at the three spiked levels (1 × LOQ, 5 × LOQ and 10 × LOQ) were in the range of 77.3–98.2% with RSDs of 0.58–11.1%. The proposed method was successfully applied for the analysis of the seven anticoagulant rodenticides in human serum.